hUMSCs-exo@Cyasterone protects the cell model of steroid-induced femur head necrosis by regulating N-glycosylation modification of CTSD-N258A - Youqiang Sun; Mengmeng Liang; Yuemeng Xing; Yifan Duan; Baogui Deng; Xiaobing Xiang (PLoS ONE, 2026)
Objective It has been demonstrated that both hUCMSC-exo and Cyasterone exhibit protective effects against steroid-induced osteonecrosis of the femoral head (SIONFH). Additionally, studies have shown that CTSD N-glycosylation influences BMSC apoptosis. Based on these findings, we aim to investigate the mechanism of hUCMSCs-exo@Cyasterone in the Dex-induced BMSCs model of SIONFH, focusing on its regulatory role in CTSD N-glycosylation during apoptosis. Methods The SIONFH cell model was induced by dexamethasone (Dex) at a concentration of 10 -6 mol/L. Experiments with hUMSCs-exo@Cyasterone and CTSD mutants were performed in the BMSC model to analyze proliferation, apoptosis, lysosomal pH, lysosomal membrane permeability, and lysosomal colocalization. Additionally, the expression of apoptosis-related proteins in BMSCs and CTSD in lysosomes and the cytoplasm were examined. Results MTT, AO staining, EDU staining, flow cytometry, and confocal microscopy revealed that hUMSCs-exo@Cyasterone attenuated the proliferation of Dex-induced BMSCs and reduced the lysosomal membrane permeability. It also decreased the expression level of apoptosis-related proteins including BID, Caspase-3, and Caspase-1, as well as the levels of CTSD in lysosomal and cytoplasm. CTSD-N258A inhibited BMSC apoptosis, enhanced the protective effect of hUMSCs-exo@Cyasterone, and promoted the lysosomal localization of CTSD and the lysosomal membrane permeability. Moreover, CTSD-N258A helped suppress the expression of apoptosis-related proteins and reduced CTSD expression in cytoplasm and lysosomes. Conclusion hUMSCs-exo@Cyasterone mitigates apoptosis in Dex-induced BMSCs, a cell model of steroid-induced femoral head necrosis, by modulating the N-glycosylation modification of CTSD-N258A.